Communications - Tannenbaum, Arnold S. (Academy of Management Journal, 1972)
The article presents comments on the article ?The Control Structure of Organizations: An Empirical Examination,? by J. Timothy McMahon and G. W. Perritt, published in the September 1971 issue. The original article criticizes the author's book ?Control in Organizations? on several grounds including that the book ignore important aspects of organizational control and that The book's research is based on a study of a sample restricted to business enterprises. The author points out that the book does cite the important facts regarding organizational controls and shows how his sample included volunteers associations and schools as well as business enterprises.